Given differential equation is "(D^2-6DD'+9D'^2)z=12x^2+36xy"
where "D = \\frac{d}{dx}, D' = \\frac{d}{dy}" .
"\\implies (D-3D')^2 z = 12 x^2 + 36 xy"
So, Auxiliary equation is "(D-3D')^2 = 0 \\implies D-3D' = 0 , D - 3D' = 0" .
Hence, Complementary function (C.F.) = "\\phi_1(y+3x) + x \\phi_2(y+3x)" .
Particular Integral (P.I.) = "\\frac{1}{(D-3D')^2} (12x^2 + 36 xy)"
"= \\frac{1}{D^2} \\left(1-\\frac{3D'}D{}\\right)^{-2} (12x^2+36xy)"
"= \\left(1+2\\frac{3D'}{D}+3\\right(\\frac{3D'}{D}\\left)^2+4\\right(\\frac{3D'}{D}\\left)^3+\u2026\\right) \\int\\int(12x^2+36xy) dxdx"
"= \\left(1+6\\frac{D'}{D}+27\\right(\\frac{D'}{D}\\left)^2+108\\right(\\frac{D'}{D}\\left)^3+\u2026\\right) \\left[ x^4 + 6 x^3 y \n \\right]"
"= x^4 + 6 x^3 y + \\frac{6}{D} (6x^3)"
"= x^4 + 6x^3 y + 9 x^4 \\\\ = 10 x^4 + 6x^3 y"
Hence, solution of given differential equation is
"z" = C.F. + P.I.
"\\implies z = \\phi_1(y+3x)+x\\phi_2(y+3x) + 10 x^4 + 6x^3 y"
Comments
Leave a comment